Spatio–temporal evolution and factors of climate comfort for urban human settlements in the Guangdong–Hong Kong–Macau Greater Bay Area - Zhou, Chunshan; Zhang, Dahao; Cao, Yongwang; Wang, Yunzhe; Zhang, Guojun (Frontiers in Environmental Science, 2022)
This study used a temperature and humidity index and a wind efficiency index at three time-scale resolutions (year, season, and month) for the first time to analyze the spatio-temporal evolution of urban climate comfort in the Guangdong–Hong Kong–Macau Greater Bay Area (GBA). Moreover, the main factors affecting human settlement climate comfort were elucidated. The annual changes in both analyzed indices in the study area exhibited fluctuating growth during 2005–2020. Moreover, the annual growth of the temperature and humidity index, as well as that of the wind efficiency index in the southern cities of the GBA was relatively fast. In contrast, the annual growth of the analyzed indices in the northern cities of the GBA was relatively slow. Overall, the climate of the human settlement environment in the GBA was found to be the most comfortable in spring and autumn, where summer and winter are characterized by hot and cold climate conditions, respectively. We did not identify any prominent change in the climate comfort of spring and autumn during 2005–2020. However, the climate comfort degree deteriorated in summer, and ameliorated in winter. At a monthly scale, the human settlement environment in the GBA was the coldest in December and the hottest in July. The urban human settlement was cold in January and February, hot in May, June, August, and September, and the most comfortable in March, April, October, and November in 2020. We analyzed the factors, affecting the climate comfort of human settlement environment in the study area and found that elevation, the percentage of gross industrial production, population scale, and construction land area were the most crucial parameters. Notably, the impact of natural factors on the climate comfort of human settlements was more significant than that of anthropogenic factors. Moreover, the related factors more strongly affected the temperature and humidity index than the wind efficiency index. Overall, our results provide data-driven guidelines for improving the climate comfort of urban human settlements in the GBA.